Otonomi VS Paternalisme: Pengambilan Keputusan Medis pada Pasien dengan Skizofrenia - Yen, Liauw Djai; Simanjuntak, Vionita; Mahardika, Danadipa Yoga; Yantoro, Felicia Cynthiadewi; Junus, Kezia Adelize Aurelia; Wijaya, Richard; Allo, Kezia Nathania Limbong; Lukito, Patricia Michelle; Dananjaya, Anna Sakurai; Wijaya, Yurike; Sugiarto, James; Mahardika, Danadipa Yoga; et al. (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 13 No 2 (2023): Indonesian Journal of Legal and Forensic Sciences, 2024)
Background: Balance between autonomy and paternalism in the context of decision making of individuals with schizophrenia is a complicated and ethical problem. Collaboration between healthcare workers, family members, and individuals with schizophrenia is crucial to ensure decision made is for the individual’s best interest whilst upholding their dignity and rights. Methods: This is a literature review study. References used are literature from journal articles, law texts, and other textbooks in Indonesian and English. Results and Discussion: In clinical practice, doctors and patients both have autonomy to make the best decision. In patients with schizophrenia, autonomy conflicts with paternalism due to errors in cognitive function and decision making. Some studies have shown that schizophrenia patients can increase their understanding through information repetition, or by using improved information delivery procedures. Loss of capacity of decision making in patients with schizophrenia is temporary and can recover with time.  Conclusion: It is important to find balance between autonomy and paternalism in medical practice. Doctors need to give clear information to patients, discussing benefits, downfalls, and risks from a certain procedure, respecting patient preference. However, doctors also have the responsibility to use their clinical judgement to give the best medical outcomes for patients.